Correction for the taxonomy of the African fern Hymenophyllum senterreanum as synonym of the newly validated Hymenophyllum mildbraedii (Hymenophyllaceae, Polypodiidae) - Dubuisson, Jean-Yves; Hennequin, Sabine (Phytotaxa, 2021)
N/A